2017
DOI: 10.1101/195297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-assembly of mutant huntingtin exon-1 fragments into large complex fibrillar structures involves nucleated branching

Abstract: Huntingtin (HTT) fragments with extended polyglutamine (polyQ) tracts self-assemble into amyloid-like fibrillar aggregates. Elucidating the fibril formation mechanism is critical for understanding Huntington's disease pathology and for developing novel therapeutic strategies.Here, we performed systematic experimental and theoretical studies to examine the selfassembly of an aggregation-prone N-terminal HTT exon-1 fragment with 49 glutamines (Ex1Q49). We demonstrate that two nucleation mechanisms control sponta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 84 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…Besides full‐length mHTT with a pathogenic polyQ tract and a largely α‐helical conformation (Guo et al ), a variety of other conformationally distinct mHTT protein species have been reported to be present in HD patient brains and disease models (Scherzinger et al ; DiFiglia et al ; Sathasivam et al ). This includes monomers and oligomers of full‐length mHTT (Sathasivam et al ; Shirendeb et al ) as well as protein species that are formed of truncated N‐terminal mHTT fragments, such as oligomers or β‐sheet‐rich, ordered fibrils (Wagner et al ). Several lines of evidence indicate efficient proteolytic cleavage of full‐length mHTT resulting in the release of N‐terminal polyQ‐containing fragments (Lunkes et al ; Landles et al ).…”
Section: Various Putatively Pathogenic Mhtt Protein Species Have Beenmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides full‐length mHTT with a pathogenic polyQ tract and a largely α‐helical conformation (Guo et al ), a variety of other conformationally distinct mHTT protein species have been reported to be present in HD patient brains and disease models (Scherzinger et al ; DiFiglia et al ; Sathasivam et al ). This includes monomers and oligomers of full‐length mHTT (Sathasivam et al ; Shirendeb et al ) as well as protein species that are formed of truncated N‐terminal mHTT fragments, such as oligomers or β‐sheet‐rich, ordered fibrils (Wagner et al ). Several lines of evidence indicate efficient proteolytic cleavage of full‐length mHTT resulting in the release of N‐terminal polyQ‐containing fragments (Lunkes et al ; Landles et al ).…”
Section: Various Putatively Pathogenic Mhtt Protein Species Have Beenmentioning
confidence: 99%
“…Apart from full‐length mHTT, truncated N‐terminal polyQ‐containing fragments may also play a critical role in HD (Davies et al ; Ast et al ). The mHTTex1 fragment has been reported to efficiently self‐assemble into higher order structures such as spherical oligomers or amyloid fibrils in vitro and in vivo (Sathasivam et al ; Sahoo et al ; Wagner et al ). It has been proposed that such protein assemblies might drive HD pathogenesis (Wanker ).…”
Section: Various Putatively Pathogenic Mhtt Protein Species Have Beenmentioning
confidence: 99%
See 3 more Smart Citations